2017
DOI: 10.1016/j.wasman.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Fate of emerging and priority micropollutants during the sewage sludge treatment: Case study of Paris conurbation. Part 1: Contamination of the different types of sewage sludge

Abstract: This article provides data on the contamination of different kinds of sludge (raw, centrifuged, digested, thermally dried sludge and sludge cake) from Paris conurbation by 71 various pollutants including pharmaceutical products (PHPs), hormones, perfluorinated acids (PFAs), linear alkylbenzene sulfonate (LAS), alkylphenols (APs), phthalates (PAEs), polycyclic aromatic hydrocarbons (PAHs) and polychlorobiphenyls (PCBs). Very high contents of LAS (0.1-10g/kg dry matter - DM) compared to other compounds were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 69 publications
5
31
0
Order By: Relevance
“…Some of these studies indicated that concentrations of DEHP change annually as a function of season and runoff, with the highest concentrations of DEHP occurring during the rainy season, the lower concentrations during the dry season, and the lowest concentrations during the transition seasons [16]. Comparing our maximum concentrations with the maximum Kd = K oc × f oc concentrations from other countries, for example, in sewage sludge from France (Paris), 29 times lower values for NP, ten times higher values for NP1EO, 57 times higher values for NP2EO, and 1.4 times higher values for DEHP were observed as those for Italy [17]. Furthermore, if comparing our maximum concentrations (for Italy) with maximum concentrations in sewage sludge samples from Greece (Athens, Patras), 160 times higher values for NP, three times higher values for the sum of NP1EO and NP2EO, and nine times higher values for DEHP were observed in the Greek sewage sludge samples [18].…”
Section: Resultssupporting
confidence: 58%
“…Some of these studies indicated that concentrations of DEHP change annually as a function of season and runoff, with the highest concentrations of DEHP occurring during the rainy season, the lower concentrations during the dry season, and the lowest concentrations during the transition seasons [16]. Comparing our maximum concentrations with the maximum Kd = K oc × f oc concentrations from other countries, for example, in sewage sludge from France (Paris), 29 times lower values for NP, ten times higher values for NP1EO, 57 times higher values for NP2EO, and 1.4 times higher values for DEHP were observed as those for Italy [17]. Furthermore, if comparing our maximum concentrations (for Italy) with maximum concentrations in sewage sludge samples from Greece (Athens, Patras), 160 times higher values for NP, three times higher values for the sum of NP1EO and NP2EO, and nine times higher values for DEHP were observed in the Greek sewage sludge samples [18].…”
Section: Resultssupporting
confidence: 58%
“…The mean concentration of PAHs in this study was 2030 dw, much greater than four sludge sites in Taiwan China (750 ng/g dw) [ 11 ], twelves sewage sludge from Beijing, China (1551 ng/g dw) [ 29 ], nineteen sewage sludge from Guangdong Province China (1276 ng/g dw) [ 7 ], but lower than the level in four sewage sludge from Harbin, Northeast China (8200 ng/g) [ 32 ], six sludge from Guangdong, China (3466 ng/g dw) [ 33 ], six Wastewater sludge from Korea (10,400 ng/g dw) [ 30 ], nineteen sludge from Madrid (5118 ng/g dw) [ 34 ], nine sewage sludge from northern and central Tunisia (11,216 ng/g dw) [ 14 ], and eleven sewage sludge from the mainland and Hong Kong, China (30,000 ng/g dw) [ 9 ]. However, the level in this study was very close to three sewage sludge from Paris (2518 ng/g dw) [ 35 ]. The European Union has proposed a limited fixed value of ten PAHs of 6000 for the implementation of sludge to agricultural fertilizer that includes Flua, BaP, IcdP, Ace, BghiP, BkF, Pyr, Phe, Flu, and BbF [ 29 ].…”
Section: Resultsmentioning
confidence: 76%
“…126 Typically, sewage sludge contains recyclable and agronomical valuable macro-and micro-nutrients. 127 However, it also includes several harmful organic and inorganic pollutants such as heavy metals (e.g., cadmium [ 128,129,130,131,132,133,134 The conversion of sewage sludge to energy (e.g., biofuels, methane, and hydrogen) and/or high-value byproducts (e.g., biofertilizers and glycerols) through biological pathways appears to be a promising and eco-friendly alternative compared to the existing physicochemical and thermal methods. 135,136,137,138 However, the major limitation to the biological conversion of sludge to energy and/or high-value byproducts at an industrial scale is the low productivity and the low yields of the conversion processes due to the complex constituents present in sewage sludge.…”
Section: Resource Recoverymentioning
confidence: 99%